1995
DOI: 10.1007/bf00202087
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of prefreezing for reducing shrinkage-related degrade in eucalypts: General considerations and review of the literature

Abstract: Summary Difficulties associated with the drying of ash eucalypts including collapse and internal checking, are discussed briefly. Prefreezing is one method that has been used successfully as a pretreatment for the drying of both hardwoods and softwoods from temperate and tropical regions.Prefreezing has produced marked reductions in shrinkage, collapse and drying degrade of the heartwood in the following species: California redwood, black walnut, black cherry, tanoak, toon, bamboo, and eucalypts. Little or no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 13 publications
2
31
1
4
Order By: Relevance
“…On the other hand, the freezing stage significantly increased the EMC of the rose gum (both the control and sample heated at 180 °C) and the Gympie messmate. The improved permeability of wood after freezing (Glossop 1994;Ilic 1995) could lead to an increase of the fractional volume of wood vessels and, consequently, to an increase of longitudinal permeability and EMC (Siau 1984). This phenomenon was also highlighted in other studies (Bal 2014;Cademartori et al 2014;Esteves et al 2014;Missio et al 2016).…”
Section: Physical Propertiesmentioning
confidence: 73%
See 2 more Smart Citations
“…On the other hand, the freezing stage significantly increased the EMC of the rose gum (both the control and sample heated at 180 °C) and the Gympie messmate. The improved permeability of wood after freezing (Glossop 1994;Ilic 1995) could lead to an increase of the fractional volume of wood vessels and, consequently, to an increase of longitudinal permeability and EMC (Siau 1984). This phenomenon was also highlighted in other studies (Bal 2014;Cademartori et al 2014;Esteves et al 2014;Missio et al 2016).…”
Section: Physical Propertiesmentioning
confidence: 73%
“…The absence of strength loss for the Gympie messmate wood can be related to its lower moisture content (~70% dry basis) during freezing, in comparison with the Rose gum wood (~140% dry basis). The mechanical changes of wood promoted by the freezing treatment were associated with compression forces against the cell wall of wood attributed to the water expansion (Ilic 1995). This phenomenon is aggravated by the faster freezing rate (Szmutku et al 2013).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-freezing produces marked reductions in shrinkage, collapse, and drying degradation of the heartwood of eucalypts; however, no significant improvement regarding internal checking was obtained (Ilic 1999b). Pre-freezing wood for 12 to 24 h at -20 °C appears to be the most practicable conditions for eucalyptus wood (Ilic 1995). There was less change in wood strength when spruce wood was subjected to freezing at -10 °C/h.…”
Section: Introductionmentioning
confidence: 94%
“…Of the three groups, one was chosen as control and the other samples underwent prefreezing for 72 h at -20 or -40 °C by household refrigerator and 596 litres of vertical cryogenic refrigerator, respectively. Some research data indicated (Ilic 1995) that being kept frozen in a freezer for 72 h could change the structure of wood. The rate of temperature decrease for freezing was -10 °C/h.…”
Section: Pre-freezing and Drying Treatmentmentioning
confidence: 99%